Outcomes of vitreoretinal surgery in retinal detachment associated with morning glory disc anomaly - Parveen Sen; Puja Maitra; Harshit Vaidya; Pramod Bhende; Kalpita Das (Indian Journal of Ophthalmology, 2021)
Purpose: Morning glory disc anomaly (MGDA) is associated with a high prevalence of retinal detachment (RD), sometimes requiring multiple surgeries. The study aimed to establish the outcomes of RD surgery in such eyes and predict factors influencing the outcome, if any. Methods: It was a retrospective observational study of 9 eyes that underwent pars plana vitrectomy (PPV) for RD associated with MGDA. Clinical and surgical details were correlated with outcomes of surgery as noted at the final follow-up. Results: PPV was performed in 9 eyes. Lensectomy was done in 5 of 9 eyes (55.5%) during PPV. Laser photocoagulation around the disc was performed in 55.5% (5/9) of the eyes. Silicone oil tamponade was used in 77.7% (7/9) of eyes and gas tamponade (14% C3F8) was used in 22.3% (2/9) of eyes. Attached retina at final visit was observed in 66% of the eyes (6/9). Two out of 3 eyes that were seen to have preoperative glial tissue at the disc had poor outcome (odds ratio 10, P = 0.16). Five out of 7 (71%) eyes that had silicone oil tamponade, had an attached retina. No identifiable breaks were noted preoperatively in 5 eyes, of which 4 (80%) had an attached retina postoperatively. Vision improved by 1 line in 67% of the eyes that underwent surgery. Conclusion: MGDA related RD presents a unique set of challenges; meticulous PPV with or without lensectomy can help in achieving a successful anatomical and functional outcome in about two-thirds of patients.